Association between casino resort employee department and responsible gambling program perceptions: a three-year follow-up study. Issue 3 (2nd September 2022) - Abarbanel, Brett; Xu, Tiange; Kraus, Shane; Gray, Heather M.; Louderback, Eric R.; LaPlante, Debi; Bernhard, Bo
ABSTRACT: This study presents results from a third wave of data collection of a longitudinal project investigating implementation of an RG program, GameSense, at MGM Resorts International (MGM), and how casino employees perceive responsible gambling (RG) efforts. Survey data at three time periods – Year 1 (baseline, N = 2, 192), Year 2 (one-year follow-up, N = 852) and Year 3 (two-year follow-up, N = 1, 114) – measured MGM employees' (1) perceptions of RG program effectiveness, (2) gambling misconceptions, and (3) perceived company support. We conducted a one-way MANCOVA on Year 3 data, with gambling industry tenure as the covariate, and a two-way MANCOVA to examine the interaction and main effects of department of employment and time period. In Year 3, Front of House Casino employees were more likely than their colleagues to perceive RG programs as effective, suggesting they can play a valuable role in refining internal program content and delivery. In investigating year-over-year changes, both perceived program effectiveness and perceived company support were lower in Year 3 than in Years 1 and 2. GameSense is designed to be part of company culture, and fluctuations in year-over-year findings suggest RG cultural change should be viewed as a long-term goal, not necessarily achieved immediately after initial program launch.